Dissolving an ambiguous partnership - Joerg Oechssler; Alex Roomets (University of Heidelberg, Department of Economics, 2023)
Two partners try to dissolve a partnership that owns an asset of ambiguous value, where the value is determined ex post by a draw from an Ellsberg urn. In a within-subject experiment, subjects make decisions in three different bargaining mechanisms: unstructured bargaining, the Texas shoot-out, and a K + 1 auction. We find that the K +1 auction is the most effcient mechanism, which is in line with theory. Free format bargaining yields a surprising number of disagreements, which are not usually observed when the partnership has a certain or risky value.
urn:nbn:de:bsz:16-heidok-338294
Keywords: C91; C72; D74; 330; Bargaining; ambiguity; experiment